Efeito de coberturas comestíveis a base de quitosana incorporadas com óleo essencial de Lippia sidoides Cham. e extrato de romã na vida útil de tomates tipo italiano (Solanum lycopersicon L.) - Araujo, Juliana Moraes Souza (2017)
Edible coatings are a good alternative to help food preservation, because they act as barrier to gases and water vapor, reducing the degradation and increasing the shelf life of the same. The aim of this study was to elaborate differents formulations of chitosan and cassava starch edible coating incorporated with Lippia sidoides (rosemary pepper) essential oil and pomegranate peel extract of the and to evaluate the effect of the same on the shelf life of italian tomatoes. The extracts, obtained with distilled water and 40 to 80% methanol concentrations, and the essential oil were evaluated for antimicrobial activity by disk diffusion test, the minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were also determined against Bacillus cereus, Bacillus subtilis, Enterococcus faecalis, Serratia marcescens, Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli bacteria. Gram-positive bacteria were more sensitive to pomegranate peel extracts, particularly the 60% methanol extract inhibited E. faecalis with the highest inhibition zone diameter (17.0 mm). On the other hand, all the bacteria were extremely sensitive to essential oil with inhibition diameters from 30.0 to 55.0 mm, being the P. aeruginosa more sensitive. The MIC values of essential oil were 25 μL/mL to E. coli and 50 μL/mL to the other bacteria. The lowest value of CBM was 50 μL/mL to E. faecalis and B. cereus, and 100 to > 400 μL/mL to other bacteria. Then, 16 formulations containing 1% cassava starch and chitosan (from 1% to 3%), essential oil (from 0.25% to 1%) and pomegranate peel extract (from 0.5 to 2%) of edible coatings were prepared. Tomatoes were coated with each formulation and stored for 12 days at 25°C. Samples of 10 tomatoes were analysed on days 1, 4, 8 and 12 for: weight loss, pH, acidity, total soluble solids, firmness, color (L, a*, b*, c, H), total aerobic mesophilic bacteria, mould and yeast counts and thermotolerant coliforms on days 1 and 12 of storage. All samples showed microbiological quality since that the maximum total bacteria, mould and yeast counts were around 10³ CFU/g and thermotolerant coliforms <3,0 NMP/g. Tomatoes coated with formulation 11 (2% chitosan, 0.5% oil and 1% extract) showed better results in relation to physical-chemical analysis, such as reduction of weight loss, constant firmness, decreased ripening and darkening of the fruit, and good appearance during the 12 days of storage.